Power-Biased Technological Change and the Rise in Earnings Inequality - Peter Skott; Frederick Guy (University of Massachusetts, Department of Economics, 2005)
New information and communication technologies, we argue, have been 'power-biased': they have allowed firms to monitor low-skill workers more closely, thus reducing the power of these workers. An efficiency wage model shows that 'power-biased technical change' in this sense may generate rising wage inequality accompanied by an increase in both the effort and unemployment of low-skill workers. The skill-biased technological change hypothesis, on the other hand, offers no explanation for the observed increase in effort. JEL Categories: J31, O33
Keywords: 330; power-biased technical change; skill bias; efficiency wages; wage inequality; work intensity